1997
DOI: 10.3109/10739689709148317
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Functional Diameter of Alveolar Septal Microvessels at the Zone I‐II Border

Abstract: In a previous study, conducted at the same value of Pinflat, but with PPA set at 15 or 20 (5 or 10 cm H2O into zone I). We estimated the capillary diameter to be 1.7 microns. Thus, the septal capillary diameter seems to increase by three- to fourfold as PPA is raised to equal Pinflat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
5
6
0
Order By: Relevance
“…Previous study on large microbubbles revealed that they coalesced in the capillary and subsequently to shrink to flow through or collapse[36]. Most microbubbles larger than 10 μm will be filtered by the pulmonary capillary[21] in consistent with our microscopic image of the microbubbles after passing through the grade 595 1/2 filter paper (Fig 3A and Fig 3B). In our study, all the mice are well tolerated with the size of the microbubbles showing no observable heart distress.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous study on large microbubbles revealed that they coalesced in the capillary and subsequently to shrink to flow through or collapse[36]. Most microbubbles larger than 10 μm will be filtered by the pulmonary capillary[21] in consistent with our microscopic image of the microbubbles after passing through the grade 595 1/2 filter paper (Fig 3A and Fig 3B). In our study, all the mice are well tolerated with the size of the microbubbles showing no observable heart distress.…”
Section: Discussionsupporting
confidence: 86%
“…The ultrasound generates inertial cavitation improving the permeability of cell membranes and enabling extracellular molecules transport directly into the cytosol[20]. In addition, large microbubbles with diameter more than 10 μm will collapse and release its contents into lung capillary bed leading to the lung targeted release[21]. Animal studies have shown that these microbubbles don't affact hemodynamic and flow at similar velocity as red blood cells if they are injected into a peripheral vein[22,23] Thus a combination of microbubbles with conventional jetPEI for gene silencing in vivo tends to be highly interested.…”
Section: Introductionmentioning
confidence: 99%
“…Upon peripheral intravenous injection, most of them can pass through the lung. Any microbubbles larger than 10 μm will be filtered by the lung capillary bed (12). Animal studies have shown that these microbubbles flow at approximately the same velocity as red blood cells, and they do not alter hemodynamics if they are injected into a peripheral vein (13, 14).…”
mentioning
confidence: 99%
“…In a subsequent report (3), we estimated the functional diameter of these vessels in zone I to be 1.7 µm. When we raised the pulmonary arterial pressure (Ppa) to equal the inflation pressure (zone I/II border), we estimated that the microvessel diameter would increase to 6-8 µm (4).…”
mentioning
confidence: 99%